Technical report: modelling of ostrich eggs using cubic hermite curve / Fatin Nadiah Hamdan, Nur Afiqah Meor Ahmad and Nurul A'qilah Mohd Hariri - Hamdan, Fatin Nadiah; Meor Ahmad, Nur Afiqah; Mohd Hariri, Nurul A'qilah (2016)
In this study Cubic Hermite Curve is applied to calculate the volume of the ostrich eggs. There are twelve different size of ostrich used as a sample to get the volume. Length, width and actual volume are the input measured to generate the calculated volume. Vernier caliper and measuring cylinder are used to get the measurement of the input. Archimedes Principal method has been used to measure an actual volume of eggs. In order to generate calculated volume, the best fitted curve of the ostrich eggs obtain by using the best fitted point in Cubic Hermite Curve equation. Besides that, the other way to determine the best fitted curve by comparison of error of three different gradient between calculated volume and actual volume.